A comprehensive and well tested energy balance for water supply systems. Issue 8 (14th September 2017) - Mamade, Aisha; Loureiro, Dália; Alegre, Helena; Covas, Dídia
Abstract: This paper presents a novel energy balance scheme and performance indicators for assessing energy efficiency in water supply systems. This assessment consists of a three-step procedure: system characterisation and data collection, energy balance calculation and energy performance indicators assessment. The main innovation is the integrated approach between energy and water balances allowing the quantification of energy inefficiencies directly associated with water losses. Comprehensive energy performance indicators can be calculated by utilities with different maturity levels allowing a fair comparison of energy efficiency between systems with different layouts and operational schemes. This energy balance scheme has been applied by 17 water utilities in Portugal. Results have shown that systems provide more than twice the minimum energy necessary to supply their consumers and, consequently, there is a significant energy saving potential: 40% through water loss reduction, 30% for changes in network operation and layout and 30% for pump inefficiency reduction.